EEG-Based Analysis of the Emotional Effect of Music Therapy on Palliative Care Cancer Patients - Ramirez, Rafael; Planas, Josep; Escude, Nuria; Mercade, Jordi; Farriols, Cristina (Frontiers in Psychology, 2018)
Music is known to have the power to induce strong emotions. The present study assessed, based on EEG data, the emotional response of terminally ill cancer patients to a music therapy intervention in a randomized controlled trial. A sample of 40 participants from the palliative care unit in the Hospital del Mar in Barcelona was randomly assigned to two groups of 20. The first group (experimental group) participated in a session of music therapy (MT), and the second group (control group) was provided with company. Based on our previous work on EEG-based emotion detection, Instantaneous emotional indicators in the form of a coordinate in the arousal-valence plane were extracted from the participants’ EEG data. The emotional indicators were analyzed in order to quantify (1) the overall emotional effect of music therapy on the patients compared to controls, and (2) the relative effect of the different music therapy techniques applied during each session. During each music therapy session, five conditions were considered: I (initial patient’s state before MT starts), C1 (passive listening), C2 (active listening), R (relaxation), and F (final patient’s state). EEG data analysis showed a significant increase in valence (p=0.0004) and arousal (p=0.003) between I and F in the experimental group. No significant changes were found in the control group. This results can be interpreted as a positive emotional effect of music therapy in advanced cancer patients. In addition, according to pre- and post-intervention questionnaire participants in the experimental group also showed a significant decrease in tiredness, anxiety and breathing difficulties, as well as an increase in levels of well-being. No equivalent changes were observed in the control group.